2019
DOI: 10.2478/ahr-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar and its Reapplication on Soil pH and Sorption Properties of Silt Loam Haplic Luvisol

Abstract: In this paper we investigate the effects of biochar alone and its reapplication and combination with N-fertilizer (1) on the soil pH, and (2) sorption parameters. The soil samples were taken during growing period in 2018 from plots with different biochar (first application in 2014 – A, reapplication in 2018 – B) at application rates: 0 t.ha−1 (B0 control), 10 t.ha−1 (B10) and 20 t.ha−1 (B20) and different nitrogen fertilization: N0 (no nitrogen) and N40 (40 kg.ha−1). Our results showed that the first applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…In our study, the unamended soil pH (KCl) was 5.7, and the biochar-amended soil pH (KCl) was 8.8. This increase could provide a more optimal soil environment for barley plants [59], with similar agronomic benefits arising from lime amendment of acid soils [30,[60][61][62]. Considering this, biochar may be a valuable tool in the management of agroecosystems and a plausible way to ameliorate acidic soils in particular, as suggested in a previous study by Horák [63].…”
Section: Soil Chemical Propertiesmentioning
confidence: 92%
“…In our study, the unamended soil pH (KCl) was 5.7, and the biochar-amended soil pH (KCl) was 8.8. This increase could provide a more optimal soil environment for barley plants [59], with similar agronomic benefits arising from lime amendment of acid soils [30,[60][61][62]. Considering this, biochar may be a valuable tool in the management of agroecosystems and a plausible way to ameliorate acidic soils in particular, as suggested in a previous study by Horák [63].…”
Section: Soil Chemical Propertiesmentioning
confidence: 92%
“…Biochar is a solid, carbon-rich product and is formed during the thermochemical decomposition of various types of organic materials (Shackley et al, 2016). Application of biochar is reported to improve soil chemical (Juriga and Šimanský, 2019;Liang et al 2006), physical (Balashov et al, 2019;Igaz et al, 2018;Toková et al, 2019;Vítková et al, 2017) and biological properties (Lehmann et al, 2011). Biochar also can increase crop yields (Kondrlová et al, 2017), reduce GHG emissions and increase soil carbon sequestration (Lehmann et al, 2006;Šimanský et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Contradictory results have been noticed in literature, where some studies reported a significant increase (Zhang et al 2019;Chintala et al 2014) and others noted no significant increment in soil pH with biochar application (Liu et al 2012;Li et al 2020). The range of changes in pH and acidity depends on soil type, soil texture, fertiliser management and type of biochar used (Juriga & Šimanský, 2019). The application of biochar plays both roles, which can decrease and increase soil pH.…”
Section: Resultsmentioning
confidence: 99%